Stability of a Cosmetic Multiple Emulsion Loaded with Green Tea Extract - Tariq Mahmood; Naveed Akhtar (The Scientific World Journal)
Multiple emulsions are excellent and exciting potential systems for the delivery of useful cosmetic agents. The work describes stability of a multiple emulsion for cosmetic purpose, loaded with extract of Camellia sinensis L. (Theaceae) in concentration of 5%. The formulation constitutes of cetyl dimethicone copolyol and polyoxyethylene (20) cetyl ether as emulsifiers and was characterised and monitored for various physicochemical aspects. Centrifugation has no devastating effect on physical destabilization/phase separation observed for 30 days. Mean globule sizes of multiple droplets were found in the range of 10.29 ± 4.4 μm to 12.77 ± 5.1 μm and of inner droplets were in the range of 0.8 ± 0.4 μm to 1.6 ± 0.8 μm. All samples exhibited shear thinning behavior with increase in shear stress. The results of the present study indicate that multiple emulsions can be used as carrier of 5% Camellia sinensis L. extract to enhance desired effects. The developed physically and chemically stable system is an effective system for targeting skin layers; however, long-term stability at elevated temperatures may be needed with suitable modifications, if required.